The Legal Status of Outsourced Workers under Indonesian Positive Law - Yuliana, Bunga; Emirzon, Joni; Flambonita, Suci (Jurnal Ilmu Hukum Kyadiren, 2026)
This study is prompted by the increasing flexibility of outsourcing arrangements in Indonesian labor law following the enactment of Law Number 6 of 2023 on the Stipulation of the Job Creation Government Regulation in Lieu of Law (Perppu), which has not been accompanied by adequate legal protection for workers. It aims to examine the legal status of outsourcing, its regulatory implications, judicial practices in worker protection, and relevant international comparisons, as well as to formulate an ideal model of protection. The study employs a normative legal research method using statutory, conceptual, and comparative approaches. The findings indicate that worker protection remains insufficient, despite the emergence of progressive approaches within the judiciary. Comparative analysis underscores the importance of the principles of equality and shared responsibility. The study concludes that policy reformulation grounded in joint liability and comprehensive protection is necessary to achieve a fair and sustainable labor system.